Effect of Machining on 3D Surface Texture and Scratch Resistance of Structural Steel - Jurickova, Eva; Zemcik, Oskar; Kolomy, Stepan; Sedlak, Josef; Hrusecka, Denisa; Chromjakova, Felicita; Sliwkova, Petra (Manufacturing Technology Journal, 2026)
This study experimentally compares how three common machining routes, turning, milling and grinding, affect the surface texture and tribological response of three structural steels (C45, 42CrMo4, 30CrMoV9) under conditions where the profile roughness Ra is deliberately aligned across routes. Areal topography was measured by coherence correlation interferometry and evaluated according to ISO 25178 (height metrics Sa, Sq, Sp, Sv, Sz, St). The bearing area curve (Abbott-Firestone) was used to derive functional descriptors Rpk, Rk and Rvk. Scratch resistance was determined on a UMT‑3 tribometer (Rockwell 120°, P = 50 N) as HSp = 8.P / w2 in accordance with ASTM G171. The results show that surfaces with comparable Ra can differ markedly in areal extremes and BAC‑derived parameters, which is reflected in scratch response. These findings support replacing sole Ra specification with areal and bearing‑curve descriptors when functional performance is critical (friction, sealing, wear).
Keywords: ISO 25178; Areal parameters; Bearing area curve (BAC); 3D surface texture; Scratch resistance; ASTM G171